Criteria for Justice of Narrators in the Book of Sunan al-Tirmidhī Persfective al-Dhahabī and Nūr Al-Dīn ‘Itr - Muhammad Amil Hikam Assaaf; Muhid; Achmadana Syachrizal M. F; Andris Nurita (al-Afkar, Journal For Islamic Studies, 2025)
This article examines the criteria for the justice of narrators in the book Sunan al-Tirmidhī from the perspectives of al-Dhahabī and Nūr al-Dīn ‘Itr. The research method employed is qualitative with a descriptive approach. The focus will be on literature analysis, collecting data through various literature reviews, describing them objectively, and subsequently analyzing them. The aim of this article is to identify the criteria for the justice of narrators as expressed by both scholars and to analyze the similarities and differences in their views. The discussion results in the conclusion that al-Dhahabī and Nūr al-Dīn have different approaches to the criteria for the justice of narrators in Sunan al-Tirmidhī. al-Dhahabī emphasizes the aspect of jarḥ wa Ta’dīl, focusing on the classification and epithets of the narrators. He centers his attention on the science of rijāl al-ḥadith. Meanwhile, Nūr al-Dīn ‘Itr adopts a more structured approach in criticizing hadith and includes specific conditions.